The peculiarities of the properties of ZnSxSe₁-x nanocrystals obtained by self-propagating high-temperature synthesis - Kovalenko, A.V.; Plakhtii, Ye.G.; Khmelenko, O.V. (Functional Materials, 2018)
ZnSxSe₁-x nanocrystals of all compounds were obtained by self-propagating high-temperature synthesis. It was found that the obtained samples had dimensions of 55±5 nm and were characterized by a mixed crystalline structure. With increase the x value the fraction of the hexagonal phase in nanocrystals decreased from 65±5 % to 30±5 %, and the fraction of the cubic phase increased in the corresponding ratios. Despite the formation of ZnSxSe₁-x solid solutions, according to RCS data, the local environment of Mn2+ impurity ions is not mixed. At a value of 0.2<x&lq;1, the Mn²⁺ ions were surrounded by sulfur ions, and at x≤0.2 it was surrounded by selenium ions. The change of the Mn²⁺ ions local environment was accompanied by an abrupt change in the value of the RCS hyperfine structure of the Mn²⁺ ions from A = 6.88-6.91 mT to A = 6.55 mT. In ZnSxSe₁-x nanocrystals with x = 1 and x = 0.9, an EPR line with g = 1.9998 was detected, which is associated with an uncontrolled impurity - Cr⁺ ions.